THE IMPORTANCE OF SILICON ORGANIC HYDROPHOBIZERS IN THE FIELD OF CONSTRUCTION (International Conference on Modern Science and Scientific Studies, 2025)
Silicon organic hydrophobizers occupy an important place in the construction industry. Their main function is to protect materials from moisture. The role of hydrophobizers is considered great in ensuring long-term durability and quality of building materials. Silicon organic hydrophobizers reduce water intake while retaining the mechanical properties of the materials. This guarantees the strength and longevity of the buildings.